1993
DOI: 10.1016/0014-5793(93)81526-6
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde‐3‐phosphate activates auto‐ADP‐ribosylation of glyceraldehyde‐3‐phosphate dehydrogenase

Abstract: Nitric oxide was recently demonstrated to stimulate ADP-ribosylation of glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Our studies on the effect of glyceraldehyde-3-phosphate (GA3P), the natural substrate of dehydrogenase activity of GAPDH. indicated GA3P to be another very potent activator of ADP-ribosylation of the enzyme. GA3P was able to activate ADP-nbosylation only m the presence of DTT. The action of GA3P was associated with inhibition of GAPDH dehydrogenase activity K, for GA3P was at least 50-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…While the distribution of ARTs and ARHs in nucleus and cytoplasm has been quite well described, the existence and distribution of ADP-ribosylating enzymes in mitochondria remains thus controversial. Five enzymes able to regulate ADP-ribosylation have so far been associated with mitochondria: SIRT4 [94,127], ARTD1, PARG, ARH3 [92,128], and MacroD1 [93,129]. ART activity has, in fact, been detected in the mitochondrial matrix, as well as the inner- and outer mitochondrial membranes [130].…”
Section: Mitochondrial Nad Biosynthesis Adp-ribosylation Crosstalmentioning
confidence: 99%
See 1 more Smart Citation
“…While the distribution of ARTs and ARHs in nucleus and cytoplasm has been quite well described, the existence and distribution of ADP-ribosylating enzymes in mitochondria remains thus controversial. Five enzymes able to regulate ADP-ribosylation have so far been associated with mitochondria: SIRT4 [94,127], ARTD1, PARG, ARH3 [92,128], and MacroD1 [93,129]. ART activity has, in fact, been detected in the mitochondrial matrix, as well as the inner- and outer mitochondrial membranes [130].…”
Section: Mitochondrial Nad Biosynthesis Adp-ribosylation Crosstalmentioning
confidence: 99%
“…MacroD1: MacroD1 has been shown to be active towards mono-ADP-ribosylated proteins, as well as toward free OAADPR, the by-product of SIRT-catalyzed de-acetylation [88,89,129]. In contrast to the four enzymes discussed above, MacroD1 has been clearly shown to predominantly localize to mitochondria [93,129]. Available transcriptome data from humans, mice, and rats [149] suggest that MacroD1 expression correlates with the energetic status of a given cell or tissue type.…”
Section: Mitochondrial Nad Biosynthesis Adp-ribosylation Crosstalmentioning
confidence: 99%
“…The level of understanding of the nature of these endogenous ADP-ribosyltransferases is poor relative to the extent ofknowledge concerning the bacterial toxins. Not all of the target proteins have been identified, and it is not clear whether all of the modifications reported require an ADP-ribosyltransferase to catalyse the reaction, or if they may proceed non-enzymically [12][13][14]. Some target proteins, such as G,a and G,a, are modified by both endogenous enzymes and bacterial toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Secreted GAPDH from Entamoeba histolytica was also found to be ADP-ribosylated [16]. The auto-catalysis of ADP-ribosylation of GAPDH is enhanced by the substrate, D-glyceraldehyde 3-phosphate [17]. Others have shown that nitric oxide promotes ADP-ribosylation [18].…”
Section: Auto-catalytic Processesmentioning
confidence: 90%